2010
DOI: 10.1007/s11325-010-0341-8
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on How common is sleep-disordered breathing in patients with idiopathic pulmonary fibrosis? Mermigkis C. et al.

Abstract: There are few recent studies on the issue of quality of sleep in interstitial lung disease [idiopathic pulmonary fibrosis (IPF)]. Early studies [1,2] showed that the patients developed significant desaturation during sleep, especially during REM sleep. In a comparative study with a healthy control group using PSG monitoring, SaO2 was reduced below 90% during 30% of sleep time. Furthermore, increased arousal, decreased sleep efficiency, and reduced Delta-sleep was found. These sleep disturbances had an effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Prior polysomnographic studies in the mid-1980s demonstrated alterations in sleep architecture and oxygen desaturation, especially during REM sleep, but not OSA, even in morbidly obese patients with ILDs [3,4]. The results of the study by Pihtili et al related to IPF patients are similar to recent studies that report increased incidence of OSA and pointed the need for high clinical suspicion for possible underlying OSA in this population [5][6][7][8]. Prior studies dating back 10-20 years probably underestimated hypopneas by using only thermal sensors and not nasal pressure transducers which are recognized as the sensitive devices for hypopnea detection that represents the majority of the observed respiratory events in IPF patients based on the newer studies.…”
supporting
confidence: 65%
“…Prior polysomnographic studies in the mid-1980s demonstrated alterations in sleep architecture and oxygen desaturation, especially during REM sleep, but not OSA, even in morbidly obese patients with ILDs [3,4]. The results of the study by Pihtili et al related to IPF patients are similar to recent studies that report increased incidence of OSA and pointed the need for high clinical suspicion for possible underlying OSA in this population [5][6][7][8]. Prior studies dating back 10-20 years probably underestimated hypopneas by using only thermal sensors and not nasal pressure transducers which are recognized as the sensitive devices for hypopnea detection that represents the majority of the observed respiratory events in IPF patients based on the newer studies.…”
supporting
confidence: 65%
“…Recently published studies [1][2][3][4] report an increased incidence of obstructive sleep apnea (OSA) in patients with idiopathic pulmonary fibrosis (IPF). Underlying and usually underdiagnosed OSA in these patients may be a reason for impaired sleep quality and may consequently have a negative influence on their daily activities and overall quality of life [5][6][7].…”
Section: Dear Editormentioning
confidence: 99%
“…Underlying and usually underdiagnosed OSA in these patients may be a reason for impaired sleep quality and may consequently have a negative influence on their daily activities and overall quality of life [5][6][7]. The absence of any effective treatment for IPF so far indicates that the recognition and treatment of generally underdiagnosed OSA in IPF patients should be a primary goal [1,2,5]. A major diagnostic problem in this population is related to the fact that the clinical presentation of OSA is often not typical, while generally accepted screening tools, such as the Epworth sleepiness scale or OSA-specific questionnaires, have several limitations to their diagnostic sensitivity [1,3].…”
Section: Dear Editormentioning
confidence: 99%
“…111,112 Briefly, in patients without lung disease, a decrease in lung volumes leads to increased upper airway resistance, increased collapsibility, and worse OSA severity. 113,114 However, whether this relationship still holds when compliance of the lung is altered in not clear, and no formal measurement of airway resistance or collapsibility has been made in IPF patients to test this hypothesis.…”
Section: Osa and Ild With Emphasis On Idiopathic Pulmonary Fibrosis mentioning
confidence: 99%